Breast Cancer Risk – From Genetics to Molecular Understanding of Pathogenesis - Fasching, P. A.; Ekici, A. B.; Wachter, D. L.; Hein, A.; Bayer, C. M.; Häberle, L.; Loehberg, C. R.; Schneider, M.; Jud, S. M.; Heusinger, K.; Rübner, M.; Rauh, C.; Bani, M. R.; Lux, M. P.; Schulz-Wendtland, R.; Hartmann, A.; Beckmann, M. W. (Geburtshilfe und Frauenheilkunde, 2013)
Several advancements over the last decade have triggered the developments in the field of breast cancer risk research. One of them is the availability of the human genome sequence along with cheap genotyping possibilities. Another is the globalization of research, which has led to the growth of research collaboration into large international consortia that facilitate the pooling of clinical and genotype data of hundreds of thousands of patients and healthy control individuals. This review concerns with the recent developments in breast cancer risk research and focuses on the discovery of new genetic breast cancer risk factors and their meaning in the context of established non-genetic risk factors. Finally the clinical application is highly dependent on the accuracy of breast cancer risk prediction models, not only for all breast cancer patients, but also for molecular subtypes, preferably for those which are associated with an unfavorable prognosis. Recently risk prediction incorporates all possible risk factors, which include epidemiological risk factors, mammographic density and genetic risk factors.
Keywords: breast cancer risk; genetic risk factors; prediction models; gene–environment interaction; BRCA